Mastering mobile learning - Udell, Chad, 1976-; Woodill, Gary. (Hoboken, NJ : John Wiley & Sons, 2014)
"Discover the strategies, tools, and technologies necessary for developing successful mobile learning programsIn the modern, rapidly-expanding mobile learning environment, only clear guidelines and state-of-the-art technologies will stand up to the challenges that lie ahead. With a smart focus that combines a proven process with all-important strategies and practical applications, Mastering Mobile Learning stands as the most modern, comprehensive resource on the subject. It also features unique technical content previously unavailable among the literature of the mobile learning field. This book will help you turn concept into reality. This book will show you best practices for obtaining and providing educational, training, and professional development content on devices like smartphones, tablets and other mobile devices. Trainers, educators, designers, instructional technologists, workplace learning professionals, and HR professionals will learn how mobile learning differs from other forms of e-learning, and will be introduced to the challenges and--more importantly--the advantages of mobile learning strategies and technologies for 21st century business environments. The book provides: An overview of mobile learning, including evolving definitions and reasons for executives to embrace this approach A discussion of the business drivers of mobile learning, advice for creating a mobile learning content strategy, and easy ways to inexpensively launch mobile learning Valuable tips on how to use unique affordances of mobile devices to better serve your learners while they are on the go Information on the ROI of mobile learning, using mobile devices as research tools, and why training in mobile development is critical An overview of the technical aspects of the design and development of mobile learning Written by experts in this burgeoning field, Mastering Mobile Learning provides a roadmap for creating the most effective learning content, strategies, and applications possible"--
"This book explains best practices for obtaining and providing educational, training, and professional development content on devices like smartphones, tablets and other mobile devices. Trainers, educators, designers, instructional technologists, workplace learning professionals, and HR professionals will learn how mobile learning differs from other forms of e-learning, and will be introduced to the challenges and--more importantly--the advantages of mobile learning strategies and technologies for 21st century business environments"--
Chapter 10: Seven Easy and Inexpensive Ways to Launch Mobile Learning1. Micro-Blogging; 2. Create a WordPress Website or Blog; 3. Start a YouTube Channel; 4. SMS (Text) Message Alerts; 5. Create a Mobile Version of Your PowerPoint Slides; 6. Audio Podcasting; 7. Poll Everywhere; Chapter 11: Building Brand Advocacy Through Mobile Learning; A Case Study of Brand Advocacy: State Farm Insurance; References; Chapter 12: Developing a Mobile Management Strategy; Bring Your Own Device (BYOD); Security and Bring Your Own Technology (BYOT); Lost/Stolen Devices and Ex-Employees.
Includes index.
Machine generated contents note: Foreword Tony Bingham Preface Introduction Part 1 Understanding Mobile Learning 1. Enterprise Mobile Learning: A Primer Gary Woodill and Chad Udell 2. The Seven Shifts in Enterprise Learning Gary Woodill 3. The Disruptive Nature of Mobile Learning John Feser 4. Why Executives Should Care About Mobile Learning John Feser 5. mLearning Is Not e-Learning on a Mobile Device John Feser Part 2 Strategic Thinking About Mobile Learning 6. The Six Ps of Mobile Learning Strategy Chad Udell 7. The Business Case for Mobile Learning John Feser 8. The New "Nomadism" as a Driver of Mobile Learning Gary Woodill 9. Creating a Mobile Learning Content Strategy Chad Udell 10. Seven Easy and Inexpensive Ways to Launch Mobile Learning John Feser 11. Building Brand Advocacy Through Mobile Learning Scott McCormick and Chad Udell 12. Developing a Mobile Management Strategy Gary Woodill and Scott McCormick 13. Change Management Strategies for Mobile Learning Scott McCormick Part 3 The Varieties of Mobile Learning Experiences 14. The Categories of Mobile Learning Content Gary Woodill and Chad Udell 15. The Unique Affordances of Mobile Learning Gary Woodill 16. Leveraging Geolocation to Make Your Content More Relevant Chad Udell 17. Incorporating Multi-Touch and Gestures into Mobile Learning Chad Udell 18. Storing Preferences and Inferring Intent in Mobile Learning Experiences Chad Udell 19. Using a Mobile Camera as a Powerful Learning Tool Chad Udell 20. Employing Mobile Device Sensors for Enhanced Learning Experiences Chad Udell 21. Alternative Reality Games as Mobile Learning John Feser 22. Using Mobile Games for Sales Training and Assessment Chad Udell 23. Voice and Messaging for Mobile Learning Chad Udell 24. Using Mobile Devices as Research Tools Gary Woodill 25. Performance Support as a Form of Mobile Learning Gary Woodill 26. Mobile Learning in "Third Spaces?: The Move to Alternative Workspaces Gary Woodill 27. The Impact of Mobile Learning on Assessment and Evaluation Gary Woodill and Chad Udell Part 4 Design and Development Processes for Mobile Learning 28. Mysteries, Heuristics, and Algorithms: Design Thinking for Mobile Learning Gary Woodill 29. Ubiquity and Mobility as Design Considerations for Mobile Learning Chad Udell 30. Design Considerations in Converting e-Learning to mLearning Chad Udell 31. The Importance of Curation for Successful Mobile Experiences Chad Udell and Gary Woodill 32. Selecting Tools for Mobile Learning Development Chad Udell 33. Instructional Design Patterns in Mobile Learning Gary Woodill 34. Creating Digital Publications for Mobile Learning Heather Ford 35. Designing for Multiple Screens in iOS Daniel Pfeiffer 36. Designing for Context Chad Udell 37. Using Mobile Devices to Leverage Social Media for Learning Gary Woodill 38. Responsive Design for Multiple Screen Formats Chad Udell 39. Design Choices for Mobile Learning Management Systems Gary Woodill 40. Maps 3.0: The New Route to Learning With Social Geospatial Data Jim Ferolo 41. Using Push Notifications to Make Mobile Learning More Useful Chad Udell 42. Improving Performance for Mobile Web and HTML5 Based Apps Daniel Pfeiffer 43. Developing with the Experience API Gary Woodill 44. Implementing Mobile Learning Metrics Chad Udell Part 5 Managing and Delivering Mobile Learning Projects 45. Managing a Mobile Learning Project Implementation Gary Woodill 46. Security in a Mobile World Chad Udell 47. Why Training in Mobile Development is Critical Jim Ferolo 48. Integrating Mobile Learning with Social Media Adam Bockler 49. Budgeting for Social and Mobile Learning Gary Woodill 50. Keeping Up with New Developments in Mobile Learning Gary Woodill About the Authors About the Contributors About ASTD Index.
Print version record and CIP data provided by publisher.
Keywords: Employees -- Training of -- Computer-assisted instruction; Mobile communication systems in education; Information technology -- Management; Employees -- Training of -- Computer-assisted instruction; Information technology -- Management; Mobile communication systems in education; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Employees -- Training of -- Computer-assisted instruction; Information technology -- Management; Mobile communication systems in education; Electronic books; Electronic books